PD-L1: Biological mechanism, function, and immunotherapy in gastric cancer - Zhang, Yingzi; Yang, Yan; Chen, Yiran; Lin, Wu; Chen, Xiangliu; Liu, Jin; Huang, Yingying; Wang, Haiyong; Teng, Lisong (Frontiers in Immunology, 2022)
Gastric cancer (GC) is the main cause of cancer incidence rate and mortality worldwide. As the main breakthrough direction, the application of immunosuppressants makes patients with GC have better prognosis, where PD-L1/PD-1 inhibitors in immunotherapy have good anti-tumor immune efficacy. Further understanding of the regulatory mechanism of PD-L1 in GC may bring substantial progress to the immunotherapy. In this review, we provide information on the endogenous and exogenous regulatory mechanisms of PD-L1 and its biological functions combined with current clinical trials of PD-L1/PD-1 inhibitors in GC. The malignant biological phenotypes caused by PD-L1 and the corresponding clinical combined treatment scheme have been reported. Identifying the biomarkers of the potential efficacy of immunotherapy and specifying the clinical immunotherapy scheme in combination with molecular characteristics of patients may maximize clinical benefits and better prognosis.